Storage and database design for UiTM Art Gallery / Nur Zafirah Ab Kadir - Ab Kadir, Nur Zafirah (2010)
Rapid advancement in Internet based applications and the wide usage of World Wide Web (WWW) has led to many challenges in information technology (IT) globally. The dawn of the new millennium has seen the births of numerous internet based applications as people are more geared toward borderless environment and communication anywhere anytime. Museums are also expected to use the internet as a medium to interact with others. One of the missions of museums is to provide access to the works of art in their collections. The existence of the World Wide Web has significantly increased the ability of museums to fulfil this mission by displaying works of art on their web sites.